Resonance energy transfer study of hemoglobin binding to model lipid membranes - Kutsenko, O. K.; Gorbenko, G. P.; Trusova, V. M. (Biophysical Bulletin, 1970)
In the present study fluorescence resonance, energy transfer (FRET) technique was employed to obtain information about the structure of hemoglobin (Hb) complexes with model lipid membranes of differentcomposition. For this purpose three membrane probes, 3-methoxybenzanthrone (MBA), 4-dimethylaminochalcone (DMC) and 6-propionyl-2-dimethylaminonaphthalene (Prodan) were assessed aspossible donors for heme moiety of the protein. Model membranes were composed of zwitterionic lipidphosphatidylcholine (PC), anionic lipid cardiolipin (CL), and cholesterol (Chol). FRET measurementswere interpreted in terms of the model of energy transfer in two-dimensional systems proposed by Fungand Stryer and further extended by Davenport et al. No FRET was observed between Prodan and Hbbecause Prodan under the employed experimental conditions was not distributed into the lipid bilayer. Inthe case of DMC, Hb-induced oxidative processes in the lipid phase hampered the estimation of Hblocation in a lipid bilayer. Therefore, structural analysis of Hb-lipid complexes was carried out usingMBA as a donor. First, the donor quantum yield, Förster radii, and fluorescence anisotropy of the probeshave been measured. Second, the amount of Hb bound to model membranes was estimated in terms of thelattice models of large ligand adsorption to lipid bilayers allowing for the possibility of protein insertioninto the membrane interior. Finally, the distance from the acceptor plane to the bilayer center and the depth of Hb penetration into the lipid bilayer were calculated. It was assumed that protein binds to membranes in the form of dimers and penetrates into the membrane interior. In neutral liposomes, Hb penetrates only to the depth of lipid headgroups. The observed higher extent of Hb penetration into Chol containing bilayer ascompared to PC liposomes may be a consequence of specific Hb-Chol interaction. In the case of PC/CLliposomes, Hb was found to insert in the non-polar membrane region. Taking into account the possibilityof forming the inverted hexagonal structures in the presence of CL, it cannot be excluded that Hb beingentrapped in such structures, translocates through the membrane. If this phenomenon takes place, deeperHb penetration into lipid bilayer might be expected. The obtained results can be useful for exactcharacterization of Hb binding to the membranes.